Molecular dynamics study on the deformation and fracture of FeCo-based alloys - Hernandez Muralles, Mario Arturo (Nanyang Technological University, 2024)
In this research, we primarily formulated interatomic potentials for the Fe-Co system using the formalism of the second nearest-neighbor modified embedded-atom method (2NN MEAM). Initially, a potential was meticulously calibrated to accurately reproduce essential thermal phases stability, structural properties, and elasticity. Moreover, point defects were deliberately introduced during the fitting process to enhance thermodynamic characteristics. Employing this refined potential in molecular dynamics (MD) simulations has led to the successful prediction of melting temperatures consistent with experimental data and the revelation of a temperature-induced B2 to L10/hcp transformation. Furthermore, the potential was applied to study the thermal effects of different FeCo phases in both bulk and multilayer films. Nevertheless, during the investigation of deformation mechanisms, the finalized potential exhibited deficiencies. With a similar approach another interatomic potential was fitted based in an optimized unary potential tailored for mechanical applications. Emphasis was placed on predicting FeCo elastic properties and antiphase boundary (APB) energies to describe the mechanical behaviors accurately. Subsequently, the Fe-Co potential was extended to encompass the Fe-Co-V ternary system by merging it with an adopted Co-V and an in-house developed Fe-V potential. Through simulations, crack nucleation and propagation mechanisms were investigated in nanocrystalline FeCo and FeCo-2V alloys under various degrees of ordering at the grain boundaries (GB) and within the grains. Notably, disordering inside grains was found to significantly impact the ductility of binary FeCo, while the mobility of antiphase domains (APD) inside grains delayed the ultimate tensile strength (UTS) and strain at fracture. The presence of V in the alloy affected the ductility, and its exclusive migration to APBs improved alloy ductility through enhanced mobility of APDs. Further advancing the study, we developed interatomic potentials for additional binary systems, including Fe-Al, Fe-Cu, Fe-Nb, Fe-W, and Co-Nb, using the 2NN MEAM formalism. These potentials were calibrated to reproduce crucial physical properties, demonstrating agreement with experimental data, CALPHAD evaluations, and first-principles calculations. These potentials were then seamlessly integrated with existing MEAM models, facilitating comprehensive explorations into the physical metallurgy of FeCo-based alloys and other multicomponent systems, including high entropy alloys (HEA). This comprehensive approach allows for a thorough exploration of the unique mechanical behaviors of these materials at the atomic scale. Considering elements experimentally proven to enhance ductility in FeCo, this study further investigates and compares the effect of V, Nb, Mo, and W on the microstructure of FeCo. Initially, the study delved into the influence on the prevalent slip directions of FeCo, revealing that the solutes have a tendency to decrease the antiphase boundary (APB) energies. Employing a combination of techniques, including Monte Carlo calculations, the study explores solute diffusion in nanocrystalline (NC) models. Notably, a distinct preference for migration towards grain boundaries (GBs) is observed, with the exception of Nb addition. Subsequent straining tests offer valuable insights into deformation behavior. Specifically, the study reveals that the addition of W extends the elastic region before the development of slip bands, while alloys containing Nb and Mo exhibit enhanced resistance to microcrack formation. In its entirety, this research offers a thorough and systematic exploration of the mechanical characteristics exhibited by both FeCo and FeCo-X (where X = V, Nb, Mo, W) alloys, facilitated by the development of novel interatomic potentials and their application in MD simulations. The findings contribute valuable insights into the behavior of complex multicomponent systems, enhancing our understanding of their mechanical characteristics at the atomic scale and providing guidelines for potential engineering applications.